Behavior of RC Beams Under Two Points Load with Different Out-of-Plane Parts - Muhammed Nura Jasim; Al-Azzawi Adel A. (Civil and Environmental Engineering)
This study focused on the out-of-plane beam behavior and the reduction caused by changes in the longitudinal axis and the out-of-plane span length in addition to the effect of adding torsion reinforcement. Five RC beams (150*200*2000) mm with constant cross section and reinforcement (except two with additional torsion reinforcement) were cast and tested under two points of monotonic load. The results showed that the existence of the out-of-plane part reduced the ultimate load by (80%), and the two out-of-plane span lengths (150mm and 300 mm) were different in behavior, that the outof-plane span (300 mm) behaved as under pure torsion while the (150 mm) behaved like under flexural and torsion loads. The worst case was for the beam with an out-of-plane part (150 mm), and the effect of adding torsion reinforcement enhanced the ultimate load by (80%) for the beam with an out-of-plane part (300 mm) whilst by (5%) for the beam with out-of-plane part (150mm).